Persistence of a Surrogate Compound on Different Surface Materials Using Fourier Transform Infrared Spectroscopy (FTIR) - สอนปลั่ง นฤมล; ชูสกุลเกรียง ศิริรัตน์; เขียวพุ่ม อรทัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Surface residue analysis plays a significant role in forensic science, particularly in drug-related cases where substances are frequently encountered at trace levels. However, legal and safety restrictions limit the use of actual controlled substances in experimental studies. This study aimed to evaluate the persistence and detectability of a surrogate compound on various surface materials. Paracetamol was selected as the surrogate compound and analyzed using Fourier Transform Infrared Spectroscopy (FTIR) with a Microscope-FTIR system operating in attenuated total reflectance (ATR) mode. The compound was transferred through direct contact onto eleven different surface types under identical controlled conditions. The results demonstrated that surface type significantly influenced detection levels. Glass slides exhibited the highest detectable signal, followed by cotton fabric and paper. Plastic surfaces showed moderate detection levels, whereas banknotes yielded relatively low detection signals. On certain surfaces, characteristic peaks were not clearly observable. These findings indicated that the physical and chemical properties of surfaces affected both the persistence and detectability of residues. The results had important implications for forensic evidence interpretation and supported the practical application of surrogate compounds in residue studies conducted under legal and safety constraints. These findings were statistically confirmed using the Kruskal–Wallis test, which demonstrated that surface type had a significant effect on detection levels (H = 30.9, df = 10, p < 0.05). Glass slides exhibited the highest mean rank, followed by cotton fabric and paper, while plastic surfaces showed moderate levels and banknotes showed lower levels.